Bioefficacy, Auto-Dissemination And Venereal Transfer Of Mosuiron 0.12P In Aedes Albopictus (Skuse) ( Diptera: Culicidae ) Population - Ng, Kin Hoong (2017)
Insect growth regulators (IGRs) offer alternatives to conventional chemical larvicides that pose problem of resistance and environmental safety. However, there is only a limited number of IGRs approved for use in mosquito control. In this current study, the effectiveness of Mosquiron® 0.12P (IGR) containing novaluron against Aedes albopictus larvae were studied in the laboratory. The IE50 (inhibition of emergence) for 24 hours, 48 hours, 72 hours and 96 hours were in the range of 3.11 x 104mg a.i./L to 3.05 x 102 mg a.i./L for the first-instar larvae. Whereas the IE95 for 24 hours, 48 hours, 72 hours and 96 hours were in the range of 2.52 x 108mg a.i. /L to 1.48 x 108 mg a.i. /L for the first-instar larvae. IE50 and IE95 increased as larval development progressed.